Characteristics of probiotic lactic acid bacteria isolated from edible birds nests as antimicrobials potential - ARI HARMAYANI; MARLINA MARLINA; ENDANG PURWATI (Society for Indonesian Biodiversity, 2024)
Abstract. Harmayani A, Marlina, Purwati E. 2024. Characteristics of probiotic lactic acid bacteria isolated from edible birds nests as antimicrobials potential. Biodiversitas 25: 1521-1527. Indonesia's export commodities include Edible Bird Nests (EBN), which possess significant economic worth. EBN is a nutrient-dense functional food that offers substantial health benefits. This study assessed the antibacterial capabilities of Lactic Acid Bacteria (LAB) extracted from EBN. This study utilized EBN sourced from three samples in West Sumatra, Indonesia, specifically in the Agam District. Use the method of experimental and collection sample EBN and identification of LAB in vitro. The isolates were examined for their morphological and biochemical characteristics. In addition, an antibacterial test was conducted along with molecular identification of the 16S rRNA gene. The findings indicated that the LAB exhibited gram-positive features, with bacilli morphology. They were also catalase-negative and classified in the homofermentative category. Antimicrobial activity was seen in all three EBN samples. BK3 edible birds’ nest isolate exhibited the highest antimicrobial activity against Listeria monocytogenes CFSN004330, with an inhibition zone diameter of 19.53 mm. It also demonstrated significant activity against Staphylococcus aureus ATCC 25923 (18.71 mm), Propionibacterium acne (18.20 mm), and Escherichia coli 0157 (14.60 mm). The molecular identification using 16S rRNA revealed that the LAB obtained from the BK3 edible birds’ nest isolate had similarities with Lacticaseibacillus paracasei strain HBUAS6004, which possesses antibacterial properties against pathogenic bacteria. There was an expectation that LAB isolates derived from EBN may serve as natural antimicrobials, providing benefits to animal and human health benefits.